An enhanced beam theory based semi-analytical method to determine the DCB mode I bridging-traction law. (1st August 2020) - Cao, Tiancheng; Zhao, Libin; Gong, Yu; Gong, Xiaojing; Zhang, Jianyu
Abstract: Delamination of composite laminates under mode I loading is usually accompanied by large scale fiber bridging. Characterization of the bridging-traction law is of significant importance in delamination simulations to account for the effect of fiber bridging in such situation. This paper proposed a semi-analytical methodology to determine the bridging-traction law of composite laminates under mode I loading. The enhanced beam theory is physically improved by considering the bending-extension coupling to model the delamination in angle-ply laminates. The strain energy release rate as well as the opening displacement of the initial crack tip, from which the bridging-traction law is derived, are characterized as a function of the crack advance and some integration constants. The effectiveness and applicability of the proposed method are validated by comparing the obtained results with those numerically and experimentally achieved. The proposed approach can conveniently determine the mode I bridging-traction law using only the fundamental material properties and experimental load-displacement data of DCB specimen, which provides some guidelines in bridging-traction law determination of composite laminates under extreme conditions requiring the environmental chambers.